Children and their development - Kail, Robert V. (Pearson Education, 2016)
Reflecting the way scientists conduct research on children’s development, Children and Their Development is organized topically, showing readers the way researchers actually study the discipline. The book’s unique and effective pedagogy focuses on practice through its accessible writing, modular format, and application-based features. It explores the theory, research, and application of modern child development from conception through adolescence. Author Robert V. Kail is a well-known and respected research in the field of child development.